Pemberdayaan Kearifan Lokal Masyarakat Adat Batak Toba dalam Mencegah Kekerasan terhadap Anak - Nanci Yosepin Simbolon; Muhammad Yasid Nasution; Muhammad Ansori Lubis (JURNAL MERCATORIA, 2019)
Children have rights guaranteed and protected by law so that the growth and development of children must be protected by every element of the country. The purpose of this study is to identify and explain the factors that cause violence against children in the family, to know and explain the forms of local wisdom contained in the Batak Toba tribe community to prevent violence against children in the family, to know and explain constraints and obstacles that arise in empowering local wisdom in the Batak Toba tribe. This research is a normative legal research and supported by empirical research. The data used in this research is secondary data. Factors causing violence against children in the family are poverty, parental education which is still lacking in terms of and patterns of child care, socio-cultural and technological advances and information and the environment. The forms of local wisdom of the Toba Batak community in preventing violence against children are pauli uhum (correcting mistakes) and manopoti sala (correcting violations). The obstacles and obstacles in empowering Batak Toba's local wisdom in preventing violence against children in the household are the concern of lawmakers and law enforcers, legal pluralism in Indonesia, the low level of socialization carried out by village and kelurahan officials.